Overview of OLAP cubes, importance, build Considerations and querying with MDX. - Devangavi, Anil Dundappa; Aggarwal, Dr Puneet (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> An OLAP cube is a method of storing data in a multidimensional form, generally for reporting purposes. The purpose of an OLAP cube is to store data in such a way that an end user can slice and dice through the data and the storage structure itself (multidimensional) while allowing for very fast access to the data. Cubes are characterized by dimensions and measures. Dimensions refer to how the data is organized and are usually made up of character fields which tell us about the data. Measures, on the other hand, are those elements in the data which quantify something (a number) and can usually be additive . The business intelligence industry uses the word "cube" because it best describes the resulting data. The query language used to interact and perform tasks with OLAP cubes is multidimensional expressions (MDX).In this paper an attempt is made to give the overview, importance and build considerations of Olap cubes. Also querying of OLAP cube with MDX is discussed. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>